Mechanical and thermal properties of LENR modified epoxy composite / Mohammed Abdullahi Abu Bakar, Wahyu Kuntjoro and S Ahmad - Abu Bakar, Mohammed Abdullahi; Kuntjoro, Wahyu; Ahmad, S. (UiTM Press, 2011)
Epoxy resins are considered as one of the most important classes of thermosetting polymers for many industrial applications and become an important matrix in polymer composites. However polymerization of this resin resulted in brittleness due to high crosslinking level. Due to this matter, many efforts have been made to improve the toughness of cured epoxy resins by the introduction of rigid particles, reactive rubbers, interpenetrating polymer networks and thermoplastics within the matrix. Incorporation of small amount of rubber is one of the approaches to improve fracture toughness of the epoxy matrix. In this work, theflexural and impact properties of liquid epoxidized natural rubber (LENR) modified epoxy composites have been studied. Addition of LENR increased the impact strength of the epoxy resin. The impact strength increased from to 18.357 kl/m2 , when modified with 5.5 phr LENR. The SEM analysis shows uniform dispersion of rubber particles within the epoxy matrix with average particle size less than 1 um.